#TITLE_ALTERNATIVE# - Dwi Ariesyady (NIM 25397013), Herto
ABSTRACT: Copper (Cu) bioaccumulate in aquatic organisms, especially, in fish, as well as in terestrial ones, which could become insafe for human consumption. An ecokinetic study on Cu in a static aquatic environment with Cu concentration of 0.75 and 1.50 mg/1 and water salinity of 250 (SI) and 1600 /mhos/cm (S2) was conducted for 40 days with the following results. The relationships between Cu concentration in fish, water, and sediment are exponential in nature with r ranging from 0,972 - 0,990. Bioaccumulation potential of Cu in Oreochromis niloticus was very high with BCF of 2759.14 and 2982.01 in fresh water and brackish water respectively. The mass balanced model for Cu were found to be x1 = 0.800x, - 0.955x, + 14.241 for S1-0.75, xj _ -0.117xa - 0.514x, + 15.291 for SI-1.50, xi = 0.3996X, - 0.3996x, + 5.647 for S2-0.75, and xi = 0.26447.E - 0.26447x, + 7.711 for S2-1.50, where xi = Cu mass in fish (mg/g), x, = Cu mass in water (mg/1), and x, = Cu mass in sediment (mg/g). The main bacteria found in fresh water sediment were Citrobacter freundii, Enterobacter agglomerans, and Pseudomonas sp. but in brackish water sediment were Pseudomonas sp., Seratia plymuthica, and Citrobacterfreundii. The LC50 value for CuSO4.5H20 by using Oreochromis niloticus with 24, 48, 72, and 96 hours exposure time were 7, 99, 4, 83, 3, 97, dan 3,49 mg/I respectively.